Intracerebral haemorrhage and hemiplegia with heterotopic ossification of the affected hip. (4th August 2015) - O'Brien, M M C; Murray, T; Keeling, F; Williams, D
Abstract : We present the case of a 72-year-old woman who developed right hemiparesis following a left frontal intraparenchymal haemorrhage. Three months following initial presentation, the patient noted poorly localised right lower quadrant pain. Following extensive investigations, a diagnosis of heterotopic ossification of the hip was made. We discuss the aetiology and pathogenesis of this uncommon entity, and discuss its relationship to ipsilateral neurological injury. The link with neurological injury can result in a delayed and atypical presentation. Early recognition and treatment are important for those caring for patients with acquired neurological deficits, and permit improved patient outcomes.